2020
DOI: 10.1083/jcb.201907087
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the contribution of Haspin and Bub1 to Aurora B function during mitosis

Abstract: Aurora B kinase is essential for faithful chromosome segregation during mitosis. During (pro)metaphase, Aurora B is concentrated at the inner centromere by the kinases Haspin and Bub1. However, how Haspin and Bub1 collaborate to control Aurora B activity at centromeres remains unclear. Here, we show that either Haspin or Bub1 activity is sufficient to recruit Aurora B to a distinct chromosomal locus. Moreover, we identified a small, Bub1 kinase–dependent Aurora B pool that supported faithful chromosome segrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 106 publications
(206 reference statements)
12
87
1
1
Order By: Relevance
“…In agreement with our results, an accompanying paper from the Lens laboratory also demonstrated that Bub1 and Haspin are individually capable of recruiting the CPC to distinct locations within the kinetochore, and furthermore, they find that neither recruitment pathway is required for kinase activity of Aurora B at kinetochores (Hadders et al, 2020). Interestingly, in their study, CRISPR/Cas9-mediated Haspin knockout combined with Bub1 kinase inhibition resulted in impaired error correction as detected by a monastrol washout assay.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our results, an accompanying paper from the Lens laboratory also demonstrated that Bub1 and Haspin are individually capable of recruiting the CPC to distinct locations within the kinetochore, and furthermore, they find that neither recruitment pathway is required for kinase activity of Aurora B at kinetochores (Hadders et al, 2020). Interestingly, in their study, CRISPR/Cas9-mediated Haspin knockout combined with Bub1 kinase inhibition resulted in impaired error correction as detected by a monastrol washout assay.…”
Section: Discussionsupporting
confidence: 90%
“…Several previous studies have suggested that chromosome localized CPC regulates error correction, bi-orientation, and checkpoint silencing (Andrews et al, 2004;Foley and Kapoor, 2013;Liu et al, 2009;Tanaka et al, 2002), although some of these functions may not require precise centromere localization (Hadders et al, 2020;Hengeveld et al, 2017). However, our analysis of multiple Incenp mutants suggests that chromosomal localization of the CPC does not promote these functions.…”
Section: Regulation Of Homolog Bi-orientation By the Cpccontrasting
confidence: 62%
“…Haspin, a highly conserved kinase in eukaryotes, is responsible for phosphorylation of histone H3T3 during mitosis [16]. Haspin kinase has been shown to be involved in sister chromatid cohesion [17] and to be necessary to localize the Chromosomal Passenger Complex (CPC) on mitotic chromatin at centromeres to activate Aurora B that regulates kinetochore-microtubule attachments [18,19,20]. In fission yeast and mammalian cells, haspin has been shown to bind the cohesin-associated protein Pds5 at centromeres and to antagonize the cohesin-unloading factor Wapl [21,22,23].…”
Section: Introductionmentioning
confidence: 99%